The Danger of Predator Journal Publication for Researchers - Himawan, Himawan; Sussolaikah, Kelik (Information Technology and Science (ITScience), 2023)
Scientific publications in the form of scientific journals are one way for researchers to share information related to the results of research that has been done, besides that scientific publications can also be used to build the reputation of researchers both in the academic and research fields. However, there is a danger of publication which until now has not been known by novice researchers who have just entered the world of scientific publications, namely publication in predatory journals. This is an important thing that needs to be known well and also must be watched out for by novice researchers. This is because predatory journals are scientific journals that are not of good quality, where the journals that are managed are only for financial gain through expensive publication fees and do not pay attention to aspects of research quality and also a good peer review process in good governance. scientific journals. In researching and writing this journal, researchers discuss some of the dangers associated with publishing predatory journals for researchers in terms of decreasing academic reputation, publication costs and also falsification of research data published in a predatory journal. In addition, researchers also look at the specific and clear characteristics of journals that can be categorized as predatory journals.